Emaze Application Based on ESD Through Animation Media to Enhance Literacy Movement - Windiyani, Tustiyana; Gani, Resyi Abdul; Sarimanah, Eri (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
This research aims to create interactive learning media based on Emaze software appropriate for grade V elementary school civic subjects. This development research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. However, this research was stopped from being developed because of the limited time required to do the research. The subject of this research is nine grade V students and one public primary school teacher, Pabuaran Cilendek Timur Bogor Elementary School. The methods of collecting data are observation and questionnaires. The instruments used in this research are the observation sheet, interview guidance, and scale of validation sheet material and media expert. This research results in interactive learning media based on Emaze, which is appropriate for civic Subjects of phase C of grade 5 elementary school. From the media expert validation, this interactive learning media gets a score percentage of 89.85% in a very appropriate category, while from the material expert validation, it gets a score of 94.43 % in a very appropriate category. The result for the individual trial gets a score percentage of 96.30% in the very practical category, while the result of the small group trial gets a score percentage of 98% in the very practical category. Through increased motivation, reading comprehension, literacy skills, collaboration, and the provision of quality reading content, Emaze can be an effective tool for encouraging reading culture and improving literacy in elementary school settings.